2017
DOI: 10.1177/0021998317704981
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the flexural response of multiscale anisogrid composite panels reinforced with carbon fibers and multi-walled carbon nanotubes

Abstract: Grid stiffened composite structures have been maturely developed in aircraft and automobile industries due to their excellence properties such as high specific strength, high specific stiffness, excellent energy absorption capability and corrosion resistance. In the current investigation, the effect of multi-walled carbon nanotubes addition in various weight percentages (0, 0.1, 0.25 and 0.4) on the flexural response of anisogrid composite panels was evaluated. For fabrication of the composite specimens, hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…[30][31][32] For example, the results from Hassanzadeh-Aghdam 33 revealed that the addition of silica nanoparticles could improve the elastic modulus in the transverse direction. Numerous researchers have established mechanical models for the stiffening effect of the applied rigid particles on the resin, and the corresponding theoretical predictions can be achieved, [34][35][36][37][38][39][40][41][42] and for different epoxy systems, the effect on the compression strength is different. The reason for this effect may be that for the low modulus DDS-cured epoxy resin system, when subjected to higher compression loads, the resin system without the addition of Al 2 O 3 nanoparticles undergoes local instability.…”
Section: Mechanical Properties Of Epoxy Resinmentioning
confidence: 99%
“…[30][31][32] For example, the results from Hassanzadeh-Aghdam 33 revealed that the addition of silica nanoparticles could improve the elastic modulus in the transverse direction. Numerous researchers have established mechanical models for the stiffening effect of the applied rigid particles on the resin, and the corresponding theoretical predictions can be achieved, [34][35][36][37][38][39][40][41][42] and for different epoxy systems, the effect on the compression strength is different. The reason for this effect may be that for the low modulus DDS-cured epoxy resin system, when subjected to higher compression loads, the resin system without the addition of Al 2 O 3 nanoparticles undergoes local instability.…”
Section: Mechanical Properties Of Epoxy Resinmentioning
confidence: 99%
“…Also, a comprehensive sensitivity analysis [ 26 ] was performed on some of the key design variables of anisogrid cylindrical shells that dominantly affect its structural reliability. Carbon nanotubes were [ 27 ] incorporated in various weight percentages and evaluated the flexural response of anisogrid composite panels. A notable improvement in the interfacial properties of matrix and fibers, flexural stiffness, and energy absorption capabilities were observed in that study.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies show that the mechanical properties of nanocomposites increase significantly by adding CNTs as fillers. 3…”
Section: Introductionmentioning
confidence: 99%